Middle Triassic autoclastic deposits from southwestern Bosnia and Herzegovina (Rudarsko-geološko-naftni zbornik, 2016)
Middle Triassic volcanic and volcaniclastic rocks have been recognized at several localities near Bosansko Grahovo, in southwestern part of Bosnia and Herzegovina in the External Dinarides. Peculiar types of autoclastic rocks were investigated. These are peperites and hyaloclastites. Regarding specific structures, mineral composition and micropetrographic characteristics it was possible to further differentiate hyaloclastites into in situ hyaloclastites and slightly resedimented hyaloclastites that represent genetic succession. All rock types occurred in a deep sea troughs that formed as a consequence of Middle Triassic extensional tectonic and rift related wrench faulting. In situ hyaloclastites and slightly resedimented hyaloclastites were formed due to quenching at the contact of lava effusions with sea water. Genesis of peperites is related to lava emplacement in unconsolidated water saturated lime mudstones that were deposited in deep sea basin. All investigated rock types represent first findings of autoclastic deposits in the External Dinarides. Biostratigraphic constraints achieved by means of conodont species Neogondolella excentrica, Paragondolella excelsa, Paragondolella trammeri and Gladigondolella tethydis indicate Late Anisian to Early Ladinian interval of the autoclastic deposits from Bosansko Grahovo.